Plasma ferritin, C-reactive protein, and adenosine deaminase levels in tuberculous lymphadenitis and pleuritis and their role in monitoring treatment response - Zaib un Nisa; Basit Zeshan; Atiqa Ambreen; Tehmina Mustafa (BMC Infectious Diseases)
Abstract Background We aimed to assess the plasma levels of ferritin, C-reactive protein (CRP), and adenosine deaminase (ADA) at baseline and their utility as biomarkers to monitor response to treatment in extrapulmonary tuberculosis (EPTB) patients. Methods Prospective measurements of ferritin, CRP, and ADA were done in unstimulated plasma samples of 92 EPTB (49 TB lymphadenitis and 43 TB pleuritis) patients registered for anti-TB treatment. Blood samples were taken at the start, 2, and 6 months of treatment, plasma levels of ferritin and CRP were measured by the enzyme-linked immunosorbent assay and ADA levels by kinetic chemistry method at each time point. Data was analyzed using SPSS version 22. Non-parametric tests were used for paired analysis and two groups’ comparison. Spearman’s rank test was used for correlation analysis. A Chi-square test was used for categorical variables. A p-value < 0.05 was considered statistically significant. Results Before the start of treatment, plasma levels of ferritin were raised in 13% and 45%, CRP in 21% and 64%, and ADA in 70% and 60% of TB lymphadenitis and pleuritis cases respectively. Levels of all three biomarkers with raised values at baseline decreased significantly with treatment at both 2 and 6 months in all patients. [Ferritin (2 months p = 0.001, 6 months p < 0.001), CRP (2 months p < 0.001, 6 months p < 0.001), ADA (2 months p = 0.039, 6 months p < 0.004)]. Plasma levels of ferritin (median 300 ng/ml range = 145–758 ng/ml) and CRP (median 11.73 mg/L, range = 10.45–17.84 mg/L) were significantly higher in TB pleuritis patients, while the levels of ADA were not significantly different among the two groups. Biosignatures generated by different combinations showed that a combination of all three biomarkers could predict treatment response in 83% and 100% of all patients at 2 and 6 months of treatment respectively. Conclusion A combination of serum ferritin, CRP, and ADA shows a promising role in monitoring response to treatment in TB lymphadenitis and TB pleuritis patients. Similar studies in larger cohorts are needed to establish a definite role of these biomarkers in EPTB patients.